(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Ecological and coenotic monitoring of plant cover on petrophytes variant of herb (forb)- bunch-grass steppe submitted in branch of Ukrainian Steppe Natural Reserve (Donetsk Region) are presents. For understanding of structural mechanisms and accompanying changes in ecotopes characteristics. The technique of computer synphytoindication was used. It promoted enough to the full characteristic of ecotope parameters under the most widespread forming features of reserve site. Sizes of ecological factors of the basic formations of reserve are designed.